Laser-Induced Fluorescence Decay of 2-Methyl-, 2-Methoxy-, and 2-Ethylnaphthlene on α-Alumina during Temperature Programmed Desorption - Bradly B. Baer; Shanan Lau; Hannah E. Ryan; K. A. Martin; A. M. Nishimura (Journal of Spectroscopy)
The decay of electronically excited molecular films of 2-methylnaphthalene (2-MN), 2-methoxynaphthalene (2-MeON), and 2-ethylnaphthalene (2-EN) on a crystal of α-alumina was monitored as a function of temperature with temperature programmed desorption (TPD) experiments. By assuming an exponential decay, the rate constants of the relaxation to the ground state were observed to have two components (±20%) by laser induced fluorescence (LIF). For the 2-MeON, 2-MN, and 2-EN excimer, the longer components were 35, 25, and 23 × 106 s−1, respectively. Rate constants for the trap fluorescence for 2-MeON, 2-MN, and 2-EN were 100, 44, and 23×106 s−1, respectively. In separate experiments, the effect of a molecule that does not fluoresce and has a lower desorption temperature than the fluorophores was studied by deposition of a bilayer. 1-Chlorohexane (1-CH) was chosen as the second layer to the fluorophore and the results gave clues to the complexity of the surface dynamics that occur as the surface is heated. For these bilayer systems, a second excimer formed during the TPD subsequent to the desorption of 1-CH, and their rates are given in parenthesis: for 2-MeON, 2-MN, and 2-EN, the long components were 30 (36), 25 (45), and 23 (42) × 106 s−1, respectively.